Mobile Banking for Empowerment Muslim Women Entrepreneur: Evidence from Asia (Indonesia and Bangladesh) - Lucky Nugroho; Syed Lutful Kabir Chowdhury (Institute for Research and Community Empowerment (LPPM TAZKIA), 2015)
Objective - Women entrepreneurs have positive contribution to the household economy in particular, and the sustainable economic development in general. Nevertheless, there are limitations in mobility for women entrepreneurs, especially in Muslim countries to conduct their business activities outside the home, which was due to concern, to take care of their children, and the values or customs, which is embraced by the local community, so that limited mobility of women entrepreneurs, not because of the Islamic religiosity. Therefore, is requires form of technology solutions for women entrepreneurs, which can reduce, the limitations.Methods - literature reviewResults - the role of mobile banking as well as branchless banking for women entrepreneurs has been shown to have a very important role to connect their access to financial services. The role of education for women, is also an important factor to improve the knowledge and ability to use technology, including mobile banking services. In addition to the phenomenon of the increasing number of women entrepreneurs and the growing literacy of women in developing countries such as Indonesia and Bangladesh, it will have an impact on increasing the professionalism of women entrepreneurs, and the demand for technology-based financial services such as mobile banking.Conclusions - Implementation of this program must have the support of all stakeholders, including the cooperation between the banks with microfinance institutions to expand the reach of the benefits of this technology. Keywords: Women Entrepreneur, mobile banking, branchless banking,